DETERMINAN TINGKAT HUTANG PADA PERUSAHAAN PUBLIK YANG BERTAHAN DALAM POSISI JAKARTA ISLAMIC INDEX SELAMA 2004-2014 - Indah Hapsari; Dewi Murdiawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
Persisting in Jakarta Islamic Index positions for more than ten years was not easy. Managing the proportion of debt at the same time making its attractive to investors was also not simple. This study aims to analyze the determinants of debt from the surviving companies in Jakarta Islamic Index positions during 2004-2014. Using multiple linear regression, the adjusted R2 was 66,3% and the results stated that managerial ownerships, institutional ownerships, independent commissioners, and liquidity could influence and control the level of debt. Meanwhile, profitability, assets structure, and company size had no significant efffect to debt. These results indicated the importance of managerial ownerships, institutional ownerships, independent commissioners, and liquidity as the determinats of debt in accordance with sharia (Bapepam-LK No.IX.A.13).